BUILD UP RATE DIVERSIFICATION IN PLANNING OF DIRECTED WELL DRILLING TRAJECTORIES IN WELL "X" FIELD "Y", WEST PAPUA: DIVERSIFIKASI BUILD UP RATE DALAM PERENCANAAN LINTASAN PENGEBORAN SUMUR TERARAH DI SUMUR “X” LAPANGAN “Y”, PAPUA BARAT - Leonardo Davinci Massolo (INTAN Jurnal Penelitian Tambang, 2024)
Well "X" in a West Papuan field is intended to be drilled directionally due to geological constraints that hinder vertically drilling trajectory. The drilling operation required standard deflection tools using bent sub which compensates drilling BUR (Buildup Rate) around 0-3 degrees/100 ft. Four BUR test variations were used in this study: 1.50/100 feet, 20/100 feet, 2,50/100 feet, and 30/100 feet. The maximum inclination angles α0max obtained with a target as deep as 9000 feet and a horizontal deviation of 3500 feet were 30.42, 29,240, 28,620, and 28,230. Out of the four scenarios in this analysis, scenario 4 with a BUR of 30/100 ft was found to be the most ideal due to its shortest length of curve in the buildup portion, after taking into account economic aspects and the drilling time necessary. However, along with the choice of a high inclination angle in a directional well, it can potentially cause technical issues such as high drag force, dogleg severity, cutting buildup, etc.